C-Reactive Protein: Clinical and Epidemiological Perspectives - Juan Salazar; María Sofía Martínez; Mervin Chávez; Alexandra Toledo; Roberto Añez; Yaquelín Torres; Vanessa Apruzzese; Carlos Silva; Joselyn Rojas; Valmore Bermúdez (Cardiology Research and Practice)
An important etiopathogenic component of cardiovascular disease is atherosclerosis, with inflammation being an essential event in the pathophysiology of all clinical pictures it comprises. In recent years, several molecules implicated in this process have been studied in order to assess cardiovascular risk in both primary and secondary prevention. C-reactive protein is a plasmatic protein of the pentraxin family and an acute phase reactant, very useful as a general inflammation marker. Currently, it is one of the most profoundly researched molecules in the cardiovascular field, yet its clinical applicability regarding cardiovascular risk remains an object of discussion, considered by some as a simple marker and by others as a true risk factor. In this sense, numerous studies propose its utilization as a predictor of cardiovascular risk through the use of high-sensitivity quantification methods for the detection of values <1 mg/L, following strict international guidelines. Increasing interest in these clinical findings has led to the creation of modified score systems including C-reactive protein concentrations, in order to enhance risk scores commonly used in clinical practice and offer improved care to patients with cardiovascular disease, which remains the first cause of mortality at the worldwide, national, and regional scenarios.